(untitled) (Proximus Journal of Sports Science and Physical Education, 2025)
The present study sought to develop an educational program utilising the cognitive acceleration technique to teach handling and suppression skills in football for individuals with disabilities (deaf and mute). The study aimed to discern the distinctions between the experimental and control research groups in acquiring these two skills, as well as to compare the outcomes of the post-tests for both groups. The researcher employed an experimental design featuring two equivalent groups with pre- and post-tests. The research cohort comprised 24 players of Specialized School for Deaf and Dumb Football in Misan Governorate for the year 2024-2025. The researcher selected 20 players, allocating 10 to the control group and 10 to the experimental group as the primary sample, while 4 additional s players were recruited for the exploratory experiment. The findings indicated a beneficial impact of the cognitive acceleration strategy on the acquisition of handling and suppressing abilities in the experimental group, in contrast to the control group that employed the conventional method. The cognitive acceleration model shown a beneficial effect on improving the reflective thinking abilities of the experimental group players on handling and suppressing skills